2020
DOI: 10.1002/agj2.20103
|View full text |Cite
|
Sign up to set email alerts
|

Straw strip mulching affects soil moisture and temperature for potato yield in semiarid regions

Abstract: Straw mulching is widely used in agriculture to conserve soil water and improve crop productivity. The effects of straw strip mulching and film mulching on dryland soil water storage and temperature, potato (Solanum tuberosum L.) growth and yield, and water use efficiency (WUE) were examined from 2014 to 2015 in the rainfed semi-arid regions of China. Field experiments were conducted with four treatments: (a) alternating strips mulched with maize (Zea mays L.) straw and bare plots with no ridges (SM); (b) alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 46 publications
(65 reference statements)
8
12
0
Order By: Relevance
“…This is in agreement with Chang et al [53], who reported that straw strip mulching reduced soil temperature during the early growth of potato. The temperature reduction under straw strip mulching in some growth stages can have a positive value for the growth and development of potato [53]. Lower soil temperature during the grain-filling period is conducive to maize, as it results in smaller diurnal temperature fluctuations, leading to lower respiration and enhanced dry matter accumulation [68,69].…”
Section: Straw Strip Mulching Affects the Temporal And Spatial Dynamics Of Soil Temperaturesupporting
confidence: 93%
See 4 more Smart Citations
“…This is in agreement with Chang et al [53], who reported that straw strip mulching reduced soil temperature during the early growth of potato. The temperature reduction under straw strip mulching in some growth stages can have a positive value for the growth and development of potato [53]. Lower soil temperature during the grain-filling period is conducive to maize, as it results in smaller diurnal temperature fluctuations, leading to lower respiration and enhanced dry matter accumulation [68,69].…”
Section: Straw Strip Mulching Affects the Temporal And Spatial Dynamics Of Soil Temperaturesupporting
confidence: 93%
“…The other mechanism of soil temperature reduction under straw strip mulching was that, by regulating water with temperature, the vigorous growth period and peak water consumption of crops will move to the precipitation concentrated season, realizing water-temperature coupling. This is in agreement with Li et al [53] and Chang et al [57], who reported that straw mulching advanced soil moisture and decreased soil temperature in some growth stages of maize and potato, and the optimized soil microenvironment promoted crop reproductive growth and development. In the present study, compared with the DRWP treatment, the V2, V6, R2, and R6 stages of the MSSM treatment were delayed by 7, 3, 3 and 3 days in 2017, and by 7, 2, 3 and 3 days in 2018, respectively.…”
Section: Straw Strip Mulching Affects the Temporal And Spatial Dynamics Of Soil Temperaturesupporting
confidence: 92%
See 3 more Smart Citations